Is decoupling economic growth from fuel consumption possible in developing countries? – A comparison of China and India. (20th August 2019) - Wang, Qiang; Jiang, Rui; Zhan, Lina
Abstract: A better understanding the coupling/decoupling of economic growth from energy demand in China and India can serve both countries and other developing countries to achieve the goal of gaining higher economic growth with less energy demand. To demonstrate the relationship between coupling/decoupling economy and energy in China and India better, this work has made following contributions: (i) analyzes the decoupling elasticity between economic growth and energy consumption by using the Tapio model, (ii) explores the five key effects (labor input, investment, energy structure, energy intensity, technology level) of decoupling elasticity by combining the Cobb Douglas (C-D) function and Log-Mean Divisia Index (LMDI) method, and (iii) evaluates the decoupling efforts by applying decoupling efforts model in China and India between 1990 and 2015. The decoupling elasticity results show China's decoupling elasticity curve is in an inverted U-shaped trend, and the decoupling elastic value is concentrated between 0 and 0.8 in most years, showing a weak decoupling state. Furthermore, the decoupling state is strong decoupling during 2014–2015, indicating China has initially achieved the decoupling of economy and energy consumption. While India's decoupling elasticity presents irregular fluctuations, indicating that India's decoupling status is not very satisfactory. The decomposition results uncover that major effects of decoupling in China and India are similar, i.e., the investment effect is the biggest driver, which contributed to a cumulative increasing impact in energy consumption in China and India by 3017.10 million tonnes oil equivalent and 675.18 million tonnes oil equivalent, respectively. Whereas the energy intensity effect is the greatest inhibiting factor, which contributed to a cumulative reduction in energy consumption in China and India by 1437.81 million tonnes oil equivalent and 139.21 million tonnes oil equivalent. The decoupling efforts results show decoupling effort in China is better than that in India. Improving energy efficiency is the leading contributor to China's decoupling efforts, while advancing technology is the major contributor to India's decoupling effort. Highlights: Better understand the coupling/decoupling economy and energy in China and India. Combining Tapio, C-D function and LMDI, and decoupling efforts to develop method. China has initially achieved the decoupling, while India's decoupling status was not very satisfactory. Major effects of decoupling in China and India were similar, while decoupling effort in China is better than in India. Leading contributor to decoupling efforts in China and India are improving efficiency and advancing technology.